Triggerless neuralgic otalgia: A case series and systematic literature review. (August 2013) - Smith, Jonathan H; Robertson, Carrie E; Garza, Ivan; Cutrer, F Michael
Background: Isolated neuralgic pain in the deep ear may arise from either nervus intermedius (NIN) or glossopharyngeal (GPN) neuralgias. Current International Headache Society (IHS) International Classification of Headache Disorders, second edition (ICHD-2) criteria for these cranial neuralgias require the presence of a characteristic trigger. Aim: The aim of this article is to report cases of triggerless neuralgic otalgia to better understand a subset of patients for whom there may be diagnostic uncertainty. Methods: Methods included an observational cohort series and systematic literature review. Results: We identified five female patients with a median age at symptom onset of 58 (range: 47 to 73). Our patients generally experienced an excellent clinical response to carbamazepine. Patients were contacted by telephone at a median follow-up duration of seven years (range: four to 32) from symptom onset, at which time carbamazepine-free remissions were reported by five of five (100%) of the patients. A systematic review of the literature on neuralgic otalgia led us to conclude that NIN was most common among young women (age < 50), and GPN across a wider range of ages of either gender. Among surgically validated cases reported in the literature, triggers were frequently absent in NIN, and variably noted in GPN. Conclusions: We conclude that the presence of a trigger is not fundamental, and may be impractical, to the diagnosis of neuralgic otalgia, but remains important for specificity between NIN and GPN.